1976
DOI: 10.1093/infdis/134.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Measles Virus III Skin Rashes by Immunofluorescence

Abstract: Specific immunofluorescence was used to detect measles virus antigen in skin rashes. Cryostat sections of punch-biopsy specimens of the skin were stained with use of hyperimmune rabbit and horse antisera to measles virus, also conjugated with fluorescein isothiocyanate, served as controls. Measles virus was specifically demonstrated in 20 of 21 biopsy specimens taken within four days after the onset of exanthema. Measles virus antigen was also found in three of five biopsy specimens from nonexanthematous skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…At that time, only SLAM/CD150-positive cells were found to be susceptible to wt MV infections. However, it remained difficult to make a final conclusion that SLAM/CD150 is the sole receptor for wt MV, because histopathological examinations of measles patients and monkeys infected with MV have revealed considerable levels of MV protein expression in the epithelia of various organs, and histopathological changes are also evident in these epithelia (Nii et al, 1964; Lightwood and Nolan, 1970; Olding-Stenkvist and Bjorvatn, 1976; Moench et al, 1988; Craighead, 2000; Figure 1). In 2003, primary cultures of human small airway epithelial cells (SAECs) were shown to be susceptible to wt MV infection (Takeuchi et al, 2003).…”
Section: Discoveries Of Cellular Receptors For MVmentioning
confidence: 99%
“…At that time, only SLAM/CD150-positive cells were found to be susceptible to wt MV infections. However, it remained difficult to make a final conclusion that SLAM/CD150 is the sole receptor for wt MV, because histopathological examinations of measles patients and monkeys infected with MV have revealed considerable levels of MV protein expression in the epithelia of various organs, and histopathological changes are also evident in these epithelia (Nii et al, 1964; Lightwood and Nolan, 1970; Olding-Stenkvist and Bjorvatn, 1976; Moench et al, 1988; Craighead, 2000; Figure 1). In 2003, primary cultures of human small airway epithelial cells (SAECs) were shown to be susceptible to wt MV infection (Takeuchi et al, 2003).…”
Section: Discoveries Of Cellular Receptors For MVmentioning
confidence: 99%
“…This study also emphasized the importance of MV spread and dissemination within the body through cell-to-cell contact rather than through the development of large multinucleated syncytia in which only a minority of the MVinfected cells present in lymphoid tissues were observed to reside. Many studies have reported extensive epithelial cell infection during measles (Kimura et al, 1975;Lightwood & Nolan, 1970; Moench et al, 1988;Olding-Stenkvist & Bjorvatn, 1976). However, in the absence of appropriate epithelial and immune cell markers, caution should be applied in using such studies to support a prominent role for epithelial cells in the pathogenesis of measles.…”
Section: Introductionmentioning
confidence: 99%
“…Although CD46, a ubiquitously expressed complement regulatory molecule, functions as a receptor for the vaccine strains of MV (8, 30), a great majority of viruses circulating in measles patients use SLAM, but not CD46, as a receptor (35,51). A recent study of MV infection in macaque monkeys also identified SLAM ϩ lymphocytes and dendritic cells as the predominantly infected cell types (6).However, pathological data from humans and experimentally infected monkeys have shown that MV antigens and syncytia are also detected in epithelial tissues in various organs, such as the skin, oral mucosa, pharynx, trachea, esophagus, intestines, and urinary bladder (5,24,26,27,31,33,34,37). Epithelial cells do not express SLAM, and wild-type (WT) strains of MV, unlike vaccine strains, do not infect epithelial cell lines.…”
mentioning
confidence: 99%
“…However, pathological data from humans and experimentally infected monkeys have shown that MV antigens and syncytia are also detected in epithelial tissues in various organs, such as the skin, oral mucosa, pharynx, trachea, esophagus, intestines, and urinary bladder (5,24,26,27,31,33,34,37). Epithelial cells do not express SLAM, and wild-type (WT) strains of MV, unlike vaccine strains, do not infect epithelial cell lines.…”
mentioning
confidence: 99%